Nurses' perception of simulation-based basic life support training in clinical practice - Maria Rente; Mafalda Costa; Manuela Pontes; Fernanda Príncipe; Liliana Mota (Instituto Politécnico de Viseu, 2021)
Introduction: Simulation-based basic life support training allows nurses to develop their skills to intervene in an emergency context, solidifying procedures and ensuring safety in practice. Objetive: Understand nurses' perception of simulation-based basic life support trainings in clinical practice. Methods: Quantitative, descriptive, and correlational study. Participants were 612 nurses from different health institutions in Portugal. The data was collected through an online questionnaire, and analyzed using the Statistical Package for the Social Sciences (version 21) with descriptive and inferential statistics, according to the nature of the variables. Results: The study demonstrates that the participants have a positive perception of the developed skills on their clinical practice, with mean values of 4.56±0.71 for understanding the basic life support algorithm, as well as 4.52±0.76 for considering it an excellent contribution to clinical practice and 4.51±0.74 for improved capacity to assess victims. Conclusion: Simulation-based training is an essential tool in the initial and continuing education of nurses. The promotion of an adequate simulation-based training plan in basic life support for nurses has a positive impact on care provision, meeting the real needs of the patient in cardiorespiratory arrest.